EVA DAN BEBERAPA VARIABEL FUNDAMENTAL PERUSAHAAN TERHADAP HARGA SAHAM - Sri Isworo Ediningsih; Nilmawati Nilmawati (University of Merdeka Malang, 2010)
Economic Value Added (EVA) as performance measure had been proven in UnitedStates. In Indonesia, EVA had been used by several companies. However, since 2001 Sawmagazine, Mark Plus Co and Maxi UI consistently made rating on 100 companies with EVA.The purpose of this study was to analyze both simultaneously and partially the influence ofEVA and several fundamental variables (CR, ROI, Size and PER) on stock price. The samplewas taken by using purposive sampling with positive EVA as criteria. There were 88 compa-nies as sample. By using multiple regression, this study found that: 1) simultaneously EVAand several fundamental variables (CR, ROI, Size and PER) significantly influenced stockprice 2) EVA, ROI and PER significantly influenced stock price and 3) CR and size company didnot significant influence stock price